METHODICAL APPROACH TO THE EMPLOYER’S BRAND ANALYSIS ON THE CASE OF IT-COMPANIES - Gontareva, Irina; Tymoshenko, Kateryna (Social Economics, 2020)
The company’s potential, its competitiveness and innovativeness directly depend on the ability to attract highly effective human resources. One of the effective ways to attract and retain resources is the brand of the employer. However, companies face many problems when building an employer’s brand, in particular, how to measure the brand, its attractiveness to potential candidates and the degree to which the company’s values match the aspirations of employees who already work in it. The aim of the study is to justify the sequence of brand level assessment among Ukrainian IT companies and determining employee loyalty to the company using the method of total ratings. It was determined that the employer’s brand is the total score that the company’s employees give according to the following criteria: pleasure from material compensation, degree of comfort of working conditions, career prospects, interest in the projects they are working on. The employer brand can be measured primarily as the loyalty of employees to the company. Work on the employer’s brand is a process that must be strategically thought out, otherwise its formation will occur spontaneously, and the evaluation results will be negative. It is proved that the assessment of an employer’s brand includes the following steps: development of a questionnaire for assessment; data collection - a survey of company employees; data processing; receiving an overall employer brand rating score. The application of the method of total ratings on the Likert scale is proposed. The advantages of this scale are the simplicity and objectivity of the assessment. A rating of IT-companies of Ukrainian employers was built, industry leaders were identified by the number of employees and by the rating of employers. The main elements and components of the employer’s brand are highlighted. The communication channels of the company’s HR-brand are considered; the tasks of employer branding are shown. Now, most employers consider working with an HR brand and an employer brand as a long-term strategic process. The high rating of the employer’s brand is one of the relevant and effective technologies for attracting the best specialists to your company. The next step is the need to focus on the interest of those employees who are already working in order to take a strong position in the IT segment in the labor market.